2008
DOI: 10.1063/1.2919521
|View full text |Cite
|
Sign up to set email alerts
|

Sound generation by head-on and oblique collisions of two vortex rings

Abstract: Sound generation by head-on and oblique collisions of two vortex rings with equal strength is investigated by a direct numerical simulation. The three-dimensional, unsteady, compressible Navier-Stokes equations are solved by a finite difference method, not only for a near-vortical field but also for a far-acoustic field. The theory of vortex sound is also applied to investigate the detailed relation between the vortex ring motion and the acoustic wave mode. Generation of two sound pressure waves, which are cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…In this case, reconnection of vortex lines occurs between the real and image vortex rings on the outer circumference of the rings. 8 For the no-slip case, the vorticity fields on the symmetric plane ͑x 1 =0͒ are presented in Fig. 14.…”
Section: A Evolution Of the Vortex Ring And Comparison With Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, reconnection of vortex lines occurs between the real and image vortex rings on the outer circumference of the rings. 8 For the no-slip case, the vorticity fields on the symmetric plane ͑x 1 =0͒ are presented in Fig. 14.…”
Section: A Evolution Of the Vortex Ring And Comparison With Experimentsmentioning
confidence: 99%
“…For the free-slip case, the grid spacings are prescribed to be the same as those in the study of Nakashima,8 in which the reliability of the grid system has been confirmed for collision of two vortex rings; the grid spacings are fixed to be ⌬x v = 0.05, ⌬x s = 1, and ⌬x b = 5, and the time step is ⌬t = 0.02. For the no-slip case, a typical example of the distributions of grid spacing is plotted against x i ͑i =1,2,3͒ in Fig.…”
Section: B Numerical Procedures and Computational Gridmentioning
confidence: 99%
See 3 more Smart Citations